Happy marriage?!. 06 - Enjoji, Maki; Thistlethwaite, Nancy (Shojo beat manga., 2014)
"Hokuto and Chiwa haven't spoken since she visited his estranged father who Hokuto believes is responsible for his mother's death. She then returns to Hokuto's birthplace to find out how his mother died. But once Chiwa learns the truth, can she help Hokuto heal the scars from his past?"--Page 4 of cover.